DAYA HAMBAT EKSTRAK DAUN MANGROVE (Rhizophora apiculata) ASAL PESISIR SUKADANA TERHADAP BAKTERI Escherichia coli (INHIBITION THE LEAF EXTRACT OF Rhizophora apiculata FROM THE SUKADANA COAST AGAINST Escherichia coli) - Muhamad Agus Wibowo; Ninda Kumala Sari; Puji Ardiningsih; Afghani Jayuska (Indonesian Journal of Pure and Applied Chemistry, 2023)
Rhizophora apiculata is a plant that is widely found in mangrove forests in Sukadana subdistrict, and has the potential to inhibit of Escherichia coli. This research aims to determine the activity of R. apiculata which grows in the Sukadana mangrove forest in inhibiting E. coli. The leaves of R. apiculata were macerated with methanol solvent, partitioned into three fractions (n-hexane fraction, dichloromethane fraction, and methanol fraction), and tested for phytochemical screening. The results of phytochemical screening of R. apiculata leaves were positive for flavonoids, alkaloids, phenolics, terpenoids, tannins, and saponins. The potential of R. apiculata leaf samples in inhibiting bacterial growth was measured by the size of the clear zone in the antibacterial test with the agar well diffusion method that uses variations in concentration, namely 250 mg/mL, 125 mg/mL, and 62.5 mg/mL. Based on the research results, it is known that R. apiculata leaves can inhibit the growth of the test bacteria with a minimum inhibitory concentration for methanol extract of 250 mg/mL. The methanol and dichloromethane fractions had minimum inhibitory concentrations of 125 mg/mL and 250 mg/mL respectively, while the n-hexane fraction did not inhibit at all test concentrations. So it can be concluded that the leaves of R. apiculata have the potential as an alternative for antibacterial active compounds